CNS-dominant human FMRP isoform rescues seizures, fear, and sleep abnormalities in Fmr1-KO mice - Hayes Wong; Alexander W.M. Hooper; Hye Ri Kang; Shiron J. Lee; Jiayi Zhao; Chanchal Sadhu; Satinder Rawat; Steven J. Gray; David R. Hampson (JCI Insight, 2023)
Fragile X syndrome is a neurodevelopmental disorder caused by the absence of the mRNA-binding protein fragile X messenger ribonucleoprotein (FMRP). Because FMRP is a highly pleiotropic protein controlling the expression of hundreds of genes, viral vector–mediated gene replacement therapy is viewed as a potential viable treatment to correct the fundamental underlying molecular pathology inherent in the disorder. Here, we studied the safety profile and therapeutic effects of a clinically relevant dose of a self-complementary adeno-associated viral (AAV) vector containing a major human brain isoform of FMRP after intrathecal injection into wild-type and fragile X–KO mice. Analysis of the cellular transduction in the brain indicated primarily neuronal transduction with relatively sparse glial expression, similar to endogenous FMRP expression in untreated wild-type mice. AAV vector–treated KO mice showed recovery from epileptic seizures, normalization of fear conditioning, reversal of slow-wave deficits as measured via electroencephalographic recordings, and restoration of abnormal circadian motor activity and sleep. Further assessment of vector efficacy by tracking and analyzing individual responses demonstrated correlations between the level and distribution of brain transduction and drug response. These preclinical findings further demonstrate the validity of AAV vector–mediated gene therapy for treating the most common genetic cause of cognitive impairment and autism in children.